2017
DOI: 10.15446/rsap.v19n2.54235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de leptospirosis en Colombia: revisión sistemática de literatura

Abstract: The systematic review allowed to determine the departments of the country where leptospirosis research is concentrated, as well as the authors with the highest number of publications on prevalence. The prevalence was found to be between 6% and 35% in humans, 41% and 60.9% in cattle, 10.3% in pigs, 12% and 47.14% in canines, 23.07 % in non-human primates, and the highest figure, between 25% and 82.7% in rodents, showing that the most frequent serovars were Icterohaemorrhagiae, Grippotyphosa and Canicola.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
8
0
4
Order By: Relevance
“…In Colombia, Leptospirosis in humans is one of the primary zoonotic diseases and is an endemic disease. A study review reports a prevalence between 6% and 35% for humans (Carreño Buitrago et al, 2017). Human studies have reported mainly serovars Icterohaemorrhagiae, Grippotyphosa, and Canicola (Carreño Buitrago et al, 2017) and Bratislava, Hebdomadis, Sejroe, and Icterohaemorrhagiae (Bello et al, 2013), some of these were found in the cattle which tested positive for leptospirosis in this study.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In Colombia, Leptospirosis in humans is one of the primary zoonotic diseases and is an endemic disease. A study review reports a prevalence between 6% and 35% for humans (Carreño Buitrago et al, 2017). Human studies have reported mainly serovars Icterohaemorrhagiae, Grippotyphosa, and Canicola (Carreño Buitrago et al, 2017) and Bratislava, Hebdomadis, Sejroe, and Icterohaemorrhagiae (Bello et al, 2013), some of these were found in the cattle which tested positive for leptospirosis in this study.…”
Section: Discussionsupporting
confidence: 52%
“…(Martins & Lilenbaum, 2017;Ullmann & Langoni, 2011). In Colombia, cases in people and animals have increased (Bello et al, 2013;Carreño Buitrago et al, 2017). Leptospirosis in humans is a notifiable disease in Colombia.…”
Section: Introductionmentioning
confidence: 99%
“…In Colombia, studies indicate human prevalence ranging from 6% to 35% ( 33 , 34 ). In Brazil, human prevalence varied between 10% and 19% in parts of the country ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through serological classification about 300 Leptospira serovars have been described, which are grouped into approximately 30 serogroups and about 200 of these serovars have been Microorganisms 2021, 9, 1897 2 of 13 considered pathogenic [6]. Colombia is an endemic country for leptospirosis with at least 500 cases every year [7]. Antioquia is the second department in Colombia with the highest number of confirmed cases of leptospirosis [7], with a seroprevalence close to 12.5% [8].…”
Section: Introductionmentioning
confidence: 99%
“…Colombia is an endemic country for leptospirosis with at least 500 cases every year [7]. Antioquia is the second department in Colombia with the highest number of confirmed cases of leptospirosis [7], with a seroprevalence close to 12.5% [8]. Leptospira interrogans and L. santarosai have been identified as the causative agents of this disease [9].…”
Section: Introductionmentioning
confidence: 99%